Opium dependency and in-hospital outcome of acute myocardial infarction - Javadi, Hamid Reza (Med J Islam Repub Iran, 2014)
Background: Impact of substance abuse on outcome of hospitalized patients with acute myocardial infarction (MI) is a frequent question. Available studies show disagreements over its impact, thus we performed this study to find a clear answer. Methods: In a cross sectional study, 304 patients (include 152 consecutive opium dependents and equal number of independents) with acute MI admitted to coronary care units (CCU) in Bou-Ali Sina Hospital of Qazvin University of Medical Science were enrolled. Data on demographics (e.g. age, sex and education), identified MI risk factor (smoking and diabetes), clinical findings (e.g. Killip class and in-hospital mortality), ECG findings (e.g. localization of infarction and arrhythmia), echocardiographic examinations (e.g. ejection fraction and regional wall motion abnormality) and laboratory findings (lipid profile, glycemic situation) were gathered. Results: The mean age was 63.01±12 years for opium users and 64.3± 10 for non-users. Educational level was higher in patients who used opium. No significant differences were found between opium users and non-users in rate of hypertension, diabetes mellitus, hyperlipidemia, and cigarette smoking. The mean duration of experienced chest pain in hospital stay was significantly higher in non-opium users compared to opium users (1.78± 0.63 vs.1.52±0.54) (p< 0.001). Higher Killip class and arrhythmia have been identified as the most important independent predictors of early in-hospital mortality (in both groups). Conclusion: The higher Killip class and age identified as the most important independent predictors of early in-hospital mortality and addiction do not act as a major risk or protecting factor in this context. Nevertheless, we believe that a more comprehensive study with follow up of patients should be carried out for evaluation of opium addicted patients, their outcome after MI, and a better decision making for their treatment.